PENGELOLAAN HOMESTAY SEBAGAI DAYA DUKUNG DESTINASI WISATA BELITUNG - Mustika Permatasari; Dilla Pratiyudha (Batara Wisnu : Indonesian Journal of Community Services, 2021)
With the deployment of Belitung as a geopark region by UNESCO, it also saw a significant increase in the growth of the homestay in Belitung. With the devotion of this society, it is expected that the homestay owner will be able to provide the best service given to guests; the homestay owner will need to gain more insight and knowledge on how to make proper and proper bed—enforcement methods. Perform community service through training of homestay management in both theory and practice. The target of dedicated activities is the homestay owner, private employees, entrepreneurs, homemakers, and tourist workers. The result of this activity is (1) a well held, smoothly executed performance, and the participants have the enthusiasm of those participating for three days and two nights; (2) participants are particularly active and follow with high motivation; and (3) trainees gain new skills in making a bed, enabling them to be implemented in the homestay they run so that it can improve the quality of service in their homestay.